Molecular docking studies, structural and spectroscopic properties of monomeric and dimeric species of benzofuran-carboxylic acids derivatives: DFT calculations and biological activities. (August 2020) - Sagaama, Abir; Noureddine, Olfa; Brandán, Silvia Antonia; Jędryka, Anna Jarczyk-; Flakus, Henryk T.; Ghalla, Houcine; Issaoui, Noureddine
Graphical abstract: Highlights: DFT calculation of 2BF and 3BF acids were carried out using B3LYP/6-311++G(d, p) method. The non-covalent interactions were investigated by Hirshfeld surface analysis. Atom in molecule (AIM) and independent gradient model (IGM) were performed. NBO, MEP and HOMO-LUMO were analyzed. Molecular docking calculation reveals the anticancer and antimicrobial activities of our compounds. Abstract: Structural optimization, molecular docking analysis, electronic and vibrational properties have been investigated for the 1-benzofuran-2-carboxylic acid (2BF) and 1-benzofuran-3-carboxylic acid (3BF) using DFT/B3LYP/6-311++G(d, p) level of theory. The theoretical parameters have a very good consistency with the experimental ones. The weak intermolecular interactions were analyzed by different tool such as: Hirshfeld surfaces, topological analysis and natural bond orbital studies. The nonlinear optical properties have been investigated. Molecular electrostatic potential and frontier molecular orbitals (FMOs) analysis have been carried out to understand the reactivity of the molecule. In addition, TD-DFT calculation is initiated to simulate the UV–vis absorption spectrum and to determine several important electronic properties like HOMO-LUMO gap energy and electronic transitions. The complete vibrational assignments and the force constants were reported for monomer and dimers of both acids. The biological activities of the tow acids have been studied via molecular docking analysis. The later calculations prove that the studied acids have an inhibitor effect against cancer and microbial diseases.